Comparative Analysis of Characteristic, Performance, and Company Value Between Consumer Non-Cyclicals and Consumer Cyclicals Sectors in Indonesia - Ni Nyoman Ayu Prapti Rahayu; I Nyoman Gede Ustriyana; Gede Mekse Korri Arisena (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
The Consumer Non-Cyclicals (CNC) and Consumer Cyclicals (CC) sectors are two important pillars of the Indonesian economy and capital market, including the agribusiness sector in general. The CNC sector has a close relationship with agribusiness, particularly in food supply and promoting agricultural activities. Meanwhile, the CC sector offers broader opportunities for agricultural downstreaming through value-added processing and manufacturing. Therefore this research aims to analyze the characteristics, company performance, and company value of these two sectors as the new insight of agribusiness in macroeconomy. This research employed the census method, and secondary data were obtained from annual and financial reports on the IDX and the company websites in 2023. This study applies quantitative descriptive analysis to examine company characteristics, including ROA, ROE, and Employee Turnover, to evaluate company performance, and uses Tobin's Q, PER, and PBV to measure company value. The contribution of this research is to provide comprehensive empirical evidence on the fundamental differences between the CNC and CC sectors, and the novelty lies in the sectoral comparison, which makes it one of the first studies in Indonesia to compare CNC and CC based on company characteristics, performance, and value, not just financial comparisons. The results show that the CNC sector performs better operationally, financially, and in human resources performance, while the CC sector shows weaker results in these three aspects. Based on company value, the CNC sector performs better on Tobin’s Q, PER, and PBV than the CC sector.